(untitled) (Stato, Chiese e pluralismo confessionale, 2024)
The Regulation of the Religious Phenomenon in the Difficult Path of the European Legal Space ABSTRACT: The problem faced by societies today is not structurally different from that which has underpinned the long process of secularisation: how to reconcile unity with diversity? How to offer equal citizenship by allowing believers of different origins and denominations, as well as non-believers (atheists, agnostics or rationalists), to coexist? The difficulty of these questions is accentuated when dealing with religious freedom and when referring to the European Union and the European Convention on Human Rights. They are archetypes of the new European legal space. The aim of this article is to understand the approach of this legal space with regard to the normative poles of equality and diversity, and with reference to the cultural and religious phenomena. SOMMARIO: 1. Introduzione. – 2. Verso un costituzionalismo deterritorializzato. – 3. Genesi e sviluppo del nuovo spazio giuridico europeo. – 4. Sistema convenzionale e fattore religioso. – 4.1 Sistema convenzionale e sistemi di relazione Stato-Chiese. – 5. L’Unione europea, il processo di integrazione e la religione. – 5.1. Le inespresse potenzialità dell’UE. – 6. Conclusioni.